SYSTEMATIC REVIEW: THE EFFECT OF AUDIT COMMITTEE QUALITY ON THE LEVEL OF RELATED PARTY TRANSACTION (RPT) DISCLOSURE IN AN INTERNATIONAL PERSPECTIVE - Hendri Ka Utama; Zuardiansyah Adi Purnama; Luk Luk Fuadah (LP2M IBK Nitro, 2026)
Related Party Transactions (RTPs) are a central issue in corporate governance, particularly in emerging markets with concentrated ownership structures like Indonesia. Using a review of relevant literature, this study identifies that RTPs often serve as a means of expropriation (tunneling) by controlling shareholders, reflecting Type II Agency Conflict and potentially reducing firm value. However, RTPs also have an efficiency dimension. To maintain the fairness of RTPs, Good Corporate Governance (GCG) mechanisms, particularly audit committees, are crucial. This study aims to conduct a Systematic Review of the Literature (SLR) using the PRISMA model to synthesize, map, and identify central themes regarding the role of RTP approval mechanisms as determinants of firm value. Based on an analysis of 17 quantitative studies, it was found that GCG, both in the form of